INTRALOBAR PULMONARY SEQUESTRATION WITH A PATENT BRONCHUS; A RARE PRESENTATION - Zafar, Usama; Majeed, Farhan Ahmed; Hussain, Zahid; Shabbir, Hassan; Farhan, Nabeela (Journal of Ayub Medical College Abbottabad, 2020)
A 25 years male working as labourer in Middle East presented with episodic chest pain and productive cough for last 10 years. There was polycystic lesion in left lower chest cavity having separate arterial supply from descending aorta on radiology. It was diagnosed as intralobar sequestration. Operative findings confirmed the presence of separate blood supply from descending aorta and patent bronchial connection of intrapulmonary sequestration to the rest of the lung parenchyma. There are only few case reports in the literature describing this entity. Posterobasal segmentectomy was done with stapling of communicating bronchus. Keywords: Intralobar; Pulmonary; Sequestration; Patent bronchus